2020
DOI: 10.3389/fneur.2020.578103
|View full text |Cite
|
Sign up to set email alerts
|

αCGRP-Induced Changes in Cerebral and Systemic Circulation; A TCD Study

Abstract: It is known that perivascular application of CGRP induces cerebral vasodilatation. However, it is unclear whether intravenous alfa CGRP (αCGRP) induces changes in cerebral and systemic hemodynamics. Therefore, we studied the influence of an αCGRP intravenous infusion at a rate of 1.5 mcg/min in 20 min on mean arterial velocity in the middle cerebral artery (vm MCA) and in the posterior cerebral artery (vm PCA) in twenty healthy subjects using transcranial Doppler (TCD). We found out that αCGRP decreased vm MCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…A study with eCGRP in healthy participants supported the vasodilatation of MCA during CGRP activity, and 60% of participants developed CGRP‐IH 5 . Recently, our study with TCD suggested vasodilatation of both MCA and the posterior cerebral artery (PCA) in healthy participants during eCGRP activity 6 . Thus, hemodynamic changes in MCA and PCA in relation to CGRP‐IH due to eCGRP could be studied using TCD.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…A study with eCGRP in healthy participants supported the vasodilatation of MCA during CGRP activity, and 60% of participants developed CGRP‐IH 5 . Recently, our study with TCD suggested vasodilatation of both MCA and the posterior cerebral artery (PCA) in healthy participants during eCGRP activity 6 . Thus, hemodynamic changes in MCA and PCA in relation to CGRP‐IH due to eCGRP could be studied using TCD.…”
Section: Introductionmentioning
confidence: 57%
“…In a previous study of our research group performed in migraineurs, 24 we found a maximal decrease in vm MCA change (point 2 of the experiment) of 67.8%, and a maximal decrease in vm PCA change of 67.1% (point 2 of the experiment), regardless of the presence of aura. After comparing migraineurs (MA and MO) to controls, 6 the maximal decrease in vm MCA change (point 2 of the experiment) was 131.1% and 45.3%, respectively. The maximal decrease in vm PCA change (point 2 of the experiment) was 169.1% and 33.1%, respectively 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the third MRA study no differences in MCA diameter were detected before and after CGRP infusion (6). In our recent study in healthy subjects we found hemodynamic responses of MCA and PCA to CGRP infusion (7). By our knowledge, so far this was the only study of PCA reactivity to CGRP infusion.…”
Section: Introductionmentioning
confidence: 73%
“…This study uses the method of Visočnik et al, and the method description partly reproduces their wording [ 8 ].…”
Section: Methodsmentioning
confidence: 99%